Genome-Wide Association Study to Find Modifiers for Tetralogy of Fallot in the 22q11.2 Deletion Syndrome Identifies Variants in the GPR98 Locus on 5q14.3. (October 2017) - Guo, Tingwei; Repetto, Gabriela M.; McDonald McGinn, Donna M.; Chung, Jonathan H.; Nomaru, Hiroko; Campbell, Christopher L.; Blonska, Anna; Bassett, Anne S.; Chow, Eva W.C.; Mlynarski, Elisabeth E.; Swillen, Ann; Vermeesch, Joris; et al.
Abstract : Background—: The 22q11.2 deletion syndrome (22q11.2DS; DiGeorge syndrome/velocardiofacial syndrome) occurs in 1 of 4000 live births, and 60% to 70% of affected individuals have congenital heart disease, ranging from mild to severe. In our cohort of 1472 subjects with 22q11.2DS, a total of 62% (n=906) have congenital heart disease and 36% (n=326) of these have tetralogy of Fallot (TOF), comprising the largest subset of severe congenital heart disease in the cohort. Methods and Results—: To identify common genetic variants associated with TOF in individuals with 22q11.2DS, we performed a genome-wide association study using Affymetrix 6.0 array and imputed genotype data. In our cohort, TOF was significantly associated with a genotyped single-nucleotide polymorphism (rs12519770, P =2.98×10 −8 ) in an intron of the adhesion GPR98 (G-protein–coupled receptor V1) gene on chromosome 5q14.3. There was also suggestive evidence of association between TOF and several additional single-nucleotide polymorphisms in this region. Some genome-wide significant loci in introns or noncoding regions could affect regulation of genes nearby or at a distance. On the basis of this possibility, we examined existing Hi-C chromatin conformation data to identify genes that might be under shared transcriptional regulation within the region on 5q14.3. There are 6 genes in a topologically associated domain of chromatin with GPR98, including MEF2C (Myocyte-specific enhancer factor 2C). MEF2C is the only gene that is known to affect heart development in mammals and might be of interest with respect to 22q11.2DS. Conclusions—: In conclusion, common variants may contribute to TOF in 22q11.2DS and may function in cardiac outflow tract development. Abstract : Supplemental Digital Content is available in the text.